2021
DOI: 10.3390/ijms222413482
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Sulfonamides Antibacterial Drugs Activity as a Result of Complexation with Ru(III): Physicochemical and Biological Study

Abstract: Antibiotic resistance is a global problem, and one promising solution to overcome this issue is using metallodrugs, which are drugs containing metal ions and ligands. These complexes are superior to free ligands in various characteristics including anticancer properties and mechanism of action. The pharmacological potential of metallodrugs can be modulated by the appropriate selection of ligands and metal ions. A good example of proper coordination is the combination of sulfonamides (sulfamerazine, sulfathiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…The EB is described by a high value of the binding constant to the DNA, and its thermodynamic characteristic of binding to the said biomolecule has been well described in other types of experiments. The sulfonamides have been selected as the main research object due to their proven antibiotic and anticancer properties. Therefore, the second small compound that has been selected for the research was sulfathiazole (STZ), a chemotherapeutic agent with a strong bacteriostatic effect. Its interaction with DNA in solutions was proven by our group using spectrophotometric titration . It was previously confirmed that STZ was also a promising ligand for the formation of complexes with transition metal ions (e.g., Ru­(III)) and that the complexation improved its antimicrobial and anticancer properties .…”
Section: Introductionmentioning
confidence: 95%
“…The EB is described by a high value of the binding constant to the DNA, and its thermodynamic characteristic of binding to the said biomolecule has been well described in other types of experiments. The sulfonamides have been selected as the main research object due to their proven antibiotic and anticancer properties. Therefore, the second small compound that has been selected for the research was sulfathiazole (STZ), a chemotherapeutic agent with a strong bacteriostatic effect. Its interaction with DNA in solutions was proven by our group using spectrophotometric titration . It was previously confirmed that STZ was also a promising ligand for the formation of complexes with transition metal ions (e.g., Ru­(III)) and that the complexation improved its antimicrobial and anticancer properties .…”
Section: Introductionmentioning
confidence: 95%
“…Bacteriostatic dosages of sulfonamides are used to prevent or limit bacterial proliferation. Sulfonamides hinder bacteria from producing folic acid, which has a bacteriostatic effect (Sánchez-Osuna et al, 2019;Nunes et al, 2020;Spisz et al, 2021). Bacteria produce folic acid on their own, by using endogenous chemicals and enzymes.…”
Section: Sulfa Drugs Used In the Treatment Sulfa Drugs Act As An Anti...mentioning
confidence: 99%
“…In the early twentieth century, antibiotics were first utilised as growth enhancers in farm animals, which led to their introduction into the everyday human diet. As a result, a significant and hitherto unforeseen phenomenon emerged: the emergence of antibiotic resistance in bacteria (Dodds, 2017;Spisz et al, 2021). Antibiotic resistance causes 2.8 million illnesses in the United States every year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through simple ligands substitution or modification, ruthenium complexes with different properties can be achieved. [ 18,28,29 ] Therefore, optimizing the properties of ruthenium complexes by changing the coordinated ligands has aroused a considerable research interest. [ 30 ] Previously, we have designed and synthesized some ruthenium complexes bearing different functional ligands with good antibacterial activities against Gram‐positive bacteria.…”
Section: Introductionmentioning
confidence: 99%